Understanding Patient and Clinician Reported Nonroutine Events in Ambulatory Surgery. Issue 2 (27th March 2023) - Salwei, Megan E.; Anders, Shilo; Slagle, Jason M.; Whitney, Gina; Lorinc, Amanda; Morley, Susan; Pasley, Jessica; DeClercq, Josh; Shotwell, Matthew S.; Weinger, Matthew B.
Abstract : Objective: Nonroutine events (NREs, i.e., deviations from optimal care) can identify care process deficiencies and safety risks. Nonroutine events reported by clinicians have been shown to identify systems failures, but this methodology fails to capture the patient perspective. The objective of this prospective observational study is to understand the incidence and nature of patient- and clinician-reported NREs in ambulatory surgery. Methods: We interviewed patients about NREs that occurred during their perioperative care using a structured interview tool before discharge and in a 7-day follow-up call. Concurrently, we interviewed the clinicians caring for these patients immediately postoperatively to collect NREs. We trained 2 experienced clinicians and 2 patients to assess and code each reported NRE for type, theme, severity, and likelihood of reoccurrence (i.e., likelihood that the same event would occur for another patient). Results: One hundred one of 145 ambulatory surgery cases (70%) contained at least one NRE. Overall, 214 NREs were reported—88 by patients and 126 by clinicians. Cases containing clinician-reported NREs were associated with increased patient body mass index ( P = 0.023) and lower postcase patient ratings of being treated with respect ( P = 0.032). Cases containing patient-reported NREs were associated with longer case duration ( P = 0.040), higher postcase clinician frustration ratings ( P < 0.001), higher ratings of patient stress ( P = 0.019), and lower patient ratings of their quality of life ( P = 0.010), of the quality of clinician teamwork ( P = 0.010), being treated with respect ( P = 0.003), and being listened to carefully ( P = 0.012). Trained patient raters evaluated NRE severity significantly higher than did clinician raters ( P < 0.001), while clinicians rated recurrence likelihood significantly higher than patients for both clinician ( P = 0.032) and patient-reported NREs ( P = 0.001). Conclusions: Both patients and clinicians readily report events during clinical care that they believe deviate from optimal care expectations. These 2 primary stakeholders in safe, high-quality surgical care have different experiences and perspectives regarding NREs. The combination of patient- and clinician-reported NREs seems to be a promising patient-centered method of identifying healthcare system deficiencies and opportunities for improvement.